The urgent need for the use of pre-exposure prophylaxis (PrEP) in the prevention of HIV/AIDS in Sub-Saharan Africa - Ayenigbara, Israel Oluwasegun (Array, 2019)
Human immunodeficiency virus (HIV) is an infection that came into existence decades back; it spread across the African countries in the late 1970s, and is currently endemic across the world. HIV is a major public health problem all over the world, as it has claimed more than 35million lives. There were around 36.9 million individuals living with HIV at the end of 2017, and Sub-Saharan Africa remains the most affected by HIV infection with 1 in 25 adults (4.1%) living with the virus, accounting for 70% of the people living with HIV worldwide. Unfortunately, Sub-Saharan Africa continues to be the continent with the highest cases of infections and deaths from HIV/AIDS even after the implementation of various HIV/AIDS prevention methods. Fortunately, pre-exposure prophylaxis (PrEP) offers the world a novel way of curtailing the HIV/AIDS epidemic, as PrEP is highly effective for preventing HIV if it is used as prescribed. This paper discusses the urgent need for the use of PrEP in the prevention of HIV/AIDS in Sub-Saharan Africa. It is a review paper in which the meaning of PrEP was discussed, people who need PrEP were identified, the rationale for the use of PrEP for the prevention of HIV/AIDS in Sub-Saharan Africa were highlighted, and probable obstacles to the successful implementation of PrEP for the prevention of HIV/AIDS in Sub-Saharan Africa were also identified. It was concluded that to achieve the 90-90-90 goals set by UNAIDS to help end the AIDS epidemic in the world, PrEP offers a new and novel way for HIV prevention, and its implementation across all African countries is urgently needed for the prevention of HIV/AIDS in Sub-Saharan Africa.